Herodotean Amestris, Sophoclean Deianeira and a Lethal Garment - Deligiorgis, Konstantinos (Literatūra, 2017)
The goal of this paper is to investigate, analyze and compare the presence and role of a garment in two literary different stories. In both occasions, a precious mantle was offered as a gift but that initiative led to disaster. Herodotean Amestris and Sophoclean Deianeira face their husband’s unfaithfulness and are both compelled to find ways to react. The details of both narrations will gradually bring to light the role as well as the influence of a garment-gift that is going to kill his receiver (Artaynte and Heracles). A present is transformed into lethal weapon and two female protagonists with different moral characters organize their plan of action in order to win back two lustful and powerful men.